Pengaruh Literasi Keuangan, Inklusi Keuangan dan Pengelolaan Keuangan Terhadap Kinerja Pelaku UMKM di Kota Bandung - Taty Sariwulan; Bingky Aresia Landarica; Novira Sabilla (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This study aims to determine the magnitude of the influence of financial literacy, financial inclusion and financial management on the performance of MSME in the city of Bandung. The research method used is a quantitative method with a descriptive and verification approach and the data used is primary data. Based on the results of the study, it is known that financial literacy has no positive effect, financial inclusion has an effect of 40.7% and financial management has an effect of 40.8% on the performance of MSME. Simultaneously, financial literacy, financial inclusion and financial management have an effect of 55.2% on the performance of MSME actors.